2016
DOI: 10.1080/15384101.2016.1195939
|View full text |Cite
|
Sign up to set email alerts
|

Impaired cell proliferation in regenerating liver of 3 β-hydroxysterol Δ14-reductase (TM7SF2) knock-out mice

Abstract: The liver is the most important organ in cholesterol metabolism, which is instrumental in regulating cell proliferation and differentiation. The gene Tm7sf2 codifies for 3 b-hydroxysterol-D 14 -reductase (C14-SR), an endoplasmic reticulum resident protein catalyzing the reduction of C14-unsaturated sterols during cholesterol biosynthesis from lanosterol. In this study we analyzed the role of C14-SR in vivo during cell proliferation by evaluating liver regeneration in Tm7sf2 knockout (KO) and wild-type (WT) mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
23
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 37 publications
0
23
0
Order By: Relevance
“…All the images were exported in TIFF, contrast and brightness were adjusted in Corel PaintShop Pro ×9 and final figures were generated with Adobe Illustrator CS6 [57]. All the images were exported in TIFF, contrast and brightness were adjusted in Corel PaintShop Pro ×9 and final figures were generated with Adobe Illustrator CS6 [57].…”
Section: Fluorescence Microscopymentioning
confidence: 99%
“…All the images were exported in TIFF, contrast and brightness were adjusted in Corel PaintShop Pro ×9 and final figures were generated with Adobe Illustrator CS6 [57]. All the images were exported in TIFF, contrast and brightness were adjusted in Corel PaintShop Pro ×9 and final figures were generated with Adobe Illustrator CS6 [57].…”
Section: Fluorescence Microscopymentioning
confidence: 99%
“…1). 5 Overall this study highlights the precisely timed cellular requirement for TG levels in the regenerating liver post PH. This heightened metabolic demand is correlated with the cell cycle in WT liver and accumulation of TG levels in Tm7sf2 KO mice at the improper time results in stress-induced arrest of the cell cycle and corresponding loss of proliferative capacity.…”
mentioning
confidence: 62%
“…For example, gene and protein expression of Cyclin D1, CDK4, and Cyclin A were constitutively repressed during all time points, in addition to loss of phospho-H3 in KO mice post PH. 5 These results were correlated with an increase in the unfolded protein response (UPR) triggered by ER stress in KO mice post PH. The authors observed an accumulation in p53 levels which induced levels of p21, a regulator of cell cycle arrest, in KO mice post PH (Fig.…”
mentioning
confidence: 94%
See 2 more Smart Citations